2014
DOI: 10.1007/s40090-014-0019-3
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion inhibition effect and adsorption behaviour of nicotinamide derivatives on mild steel in hydrochloric acid solution

Abstract: Background A new class of nicotinamide derivatives viz., N-((1H-pyrrol-2-yl)methylene)nicotinamide, N-((methyl-(phenyl)amino)methylene)nicotinamide, N-nicotinoylbenzimidothioic acid and N-(4-(methylthio)benzylidene)nicotinamide have been synthesized and their corrosion inhibition effect on mild steel in 0.5 M HCl was investigated by mass loss, Tafel polarization technique and AC impedance measurements. Results The inhibition efficiency of the inhibitors on mild steel in 0.5 M HCl has been studied based on conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(21 citation statements)
references
References 51 publications
1
19
0
1
Order By: Relevance
“…The obtained E corr value in case of CCA being shifted toward the lower side of 85 mV, confirmed that CCA acts as a mixed inhibitor type and has control over not only anodic metal dissolution, but cathodic hydrogen evolution also [26,29]. Besides, as observed from Table 1 the cathodic and anodic slope (β c and β a ) values did not show much change, which indicated that CCA influences the anodic and cathodic reaction kinetics without affecting the reaction mechanism [30].…”
Section: Potentiodynamic Polarization Studiessupporting
confidence: 63%
“…The obtained E corr value in case of CCA being shifted toward the lower side of 85 mV, confirmed that CCA acts as a mixed inhibitor type and has control over not only anodic metal dissolution, but cathodic hydrogen evolution also [26,29]. Besides, as observed from Table 1 the cathodic and anodic slope (β c and β a ) values did not show much change, which indicated that CCA influences the anodic and cathodic reaction kinetics without affecting the reaction mechanism [30].…”
Section: Potentiodynamic Polarization Studiessupporting
confidence: 63%
“…Lowering in corrosion rate (CR) by rising Tetraclinis articulata extract doses is as a result of the fact that the metal surface coverage (θ) become larger via the adsorption of inhibitor molecules 27 . The reduce in CR possibly with rising in temperature via adsorption rate of Tetraclinis articulata extract on the MS surface has been raised at higher temperatures 28 .…”
Section: Resultsmentioning
confidence: 99%
“…Energy Dispersive Analysis of X-rays is the most powerful method to find out the formation of protective film on the metal surface 21,22 .…”
Section: Energy Dispersive X-ray Analysis (Edx)mentioning
confidence: 99%